Narratives and Rituals of the Nightmare Hag in Scandinavian Folk Belief - Raudvere, Catharina. author. aut Link
XI, 310 p. 14 illus.
Keywords: This books explores varying conceptions of the Nightmare hag, mara, in Scandinavian folk belief. What began as observations of some startling narratives preserved in folklore archives where sex, violence and curses are recurring themes gradually led to questions as to how rural people envisaged good and evil, illness and health, and cause and effect. At closer reading, narratives about the mara character involve existential themes, as well as comments on gender and social hierarchy. This monograph analyses how this female creature was conceived of in oral literature and everyday ritual practice in pre-industrial Scandinavia, and what role she played in a larger pattern of belief in witchcraft and magic.